The trend of competitive balance in Iran football Premier League: A survey of 1995-2009 seasons - Naghshbandi, S.; Yousefi, B.; Boroujerdi, S. S.; Jabari, N. (International Journal of Sports Science and Engineering, 2011)
Competitive balance refers to the balance in sport capabilities of teams. The more competitive balance is among teams comprising league, the harder predicting the games is and finally resulting in more attractive league. The purpose of this study was to investigate changes of competitive balance in Iran pro league from 1995 to 2009. Data were secondary derived from the final tables of 1995-2009. Data analysis was based on C5ICB index. For easier analysis, the findings (C5ICB) of research had been presented as 3 five year periods; first five years (1995-1999): 128, second five years (2000-2004): 131, third five years (2005-2009): 129.6. It had the most balance in first five years. C5ICB demonstrated least balance in second five years. High competitive balance resulted in sever competition leads to high quality of league and better function of teams. Today bipolar condition of Iranian football (clubs of Piroozi and Esteqlal) has changed. Football is not Tehran-oriented in Iran anymore and developed in cities such as Isfahan, Kerman and Tabriz.